Applying geo-spatial analysis in community needs assessment: Implications for planning and prioritizing based on data. (October 2016) - Baig, Kamran; Shaw-Ridley, Mary; Munoz, Oscar J.
Highlights: Applying spatial technology to traditional community needs assessment (CNA). Using conceptual framework for integrating CNA and capacity building. Maximize delivery of optimal healthcare services for poor and underserved areas. Assisting planners and policy makers with gap analysis in program planning. Abstract: Background: Colonias are sub standardized and unincorporated areas located along the US-Mexico border, with severely lacking infrastructure. Residents have poor health and limited availability, accessibility and/or utilization of healthcare services in the region. Methods: Using 2006–2007 community needs assessment (CNA) surveys collected by the Center for Housing and Urban Development of Texas A&M University, 410 randomly selected surveys from Hidalgo County, Texas were analyzed. Descriptive and spatial analyses were performed and Odds ratio (OR) was calculated. Results: Out of 410 surveys, 333 were geo-coded to identify areas most in need of dental and vision care. Two hospitals existed within 5 miles radius of the mean centers for the two areas. Distance to health care facility was not statistically predictive of the need of dental care OR = 0.96 (95% CI = 0.855-1.078, p value = 0.492) and vision care OR = 1.083 (95% CI = 0.968-1.212, p value = 0.164). Conclusion: Integrating spatial analysis and CNA enhances planning to improve service accessibility and utilization in underserved areas.